(untitled) (Fiep Bulletin - online, 2013)
The aim of this study was to investigate how will health theme issue is addressed in school physical education classes in the State School of Negreiros Vidal. Therefore, there was at first a documentary research with the (Political Pedagogical Project - PPP), and a second phase was conducted exploratory research with the school community. From the document analysis verified that includes the school (PPP) broadly cross the subject health. However, the interview with the actors schoolchildren showed that in practice the school addresses the issue of a limited health and education classes the theme is not addressed. The results show that the school researched the topic of health is part of the PPP school. However, in practice it worked when there is fragmented vision hygienist in health and physical education classes does not compose the contents worked.